Alfuzosin-Induced Autoimmune Hepatitis: A Rare Case Report - Ergin, Mustafa; Moral, Kenan; Karataş, Ali; Kekilli, Murat (Turkish Journal of Gastroenterology, 2025)
Cite this article as: Ergin M, Moral K, Karataş A, Kekilli M. Alfuzosin-induced autoimmune hepatitis: A rare case report. Turk J Gastroenterol. 2025;36(12):885-886.